Glucocorticoid dysfunction in children with severe malaria - Vandermosten, Leen; Prenen, Fran; Fogang, Balotin; Dagneau de Richecour, Pauline; Knoops, Sofie; Donkeu, Christiane Josiane; Nguefack, Cathy Doric Piemba; Taguebue, Jean-Voisin; Ndombo, Paul Koki; Ghesquière, Bart; Ayong, Lawrence; Van den Steen, Philippe E. (Frontiers in Immunology, 2023)
Malaria remains a widespread health problem with a huge burden. Severe or complicated malaria is highly lethal and encompasses a variety of pathological processes, including immune activation, inflammation, and dysmetabolism. Previously, we showed that adrenal hormones, in particular glucocorticoids (GCs), play critical roles to maintain disease tolerance during Plasmodium infection in mice. Here, GC responses were studied in Cameroon in children with uncomplicated malaria (UM), severe malaria (SM) and healthy asymptomatic controls (HCAC). Total cortisol levels increased in malaria patients with clinical malaria compared to HCAC and were higher in the SM versus UM group, while cortisol binding globulin levels were unchanged and adrenocorticotropic hormone (ACTH) levels were heterogeneous. To determine the sensitivity of leukocytes to GC signaling on a transcriptional level, we measured the ex vivo induction of glucocorticoid induced leucine zipper (GILZ) and FK506-binding protein 5 (FKBP5) by GCs in human and murine leukocytes. Induction of both genes by GCs was significantly reduced in patients with clinical malaria compared to AC and in malaria-infected mice compared to uninfected controls. Targeted tracer metabolomics on peripheral blood mononuclear cells (PBMCs) indicated an increased activity in the pentose phosphate pathway in the patients, but this was not affected by ex vivo stimulation with physiological levels of hydrocortisone. Interestingly, hydrocortisone induced increased levels of cAMP in HCAC, but not in clinical malaria patients. Altogether, this study shows that patients with SM have increased cortisol levels, but also a decreased sensitivity to GCs, which may clearly contribute to the severity of disease.